Geochemical characteristics of stream sediments from an urban-volcanic zone, Central Mexico: Natural and man-made inputs - Shruti, V.; Jonathan, M.; Rodríguez-Espinosa, P.; Ramasamy, Nagarajan; Escobedo-Urias, D.; Morales-García, S.; Martínez-Tavera, E. (Elsevier GmbH - Urban und Fischer, 2016)
Geochemical characteristics of stream sediments [n = 31; Upstream section: Zahuapan River (1-12) and Atoyac River (13-20); Downstream section (21-31)] from Atoyac River basin of Central Mexico have been evaluated. The study focuses on the textural, petrography and chemical composition of the fluvial sediments with the aim of analyzing their provenance, the chemical weathering signature and their potential environmental effects. The fluvial sediments are mostly composed of sand and silt sized particles dominated by plagioclase, pyroxenes, amphiboles, K-feldspar, biotite, opaque and quartz. The sediments were analyzed for determination of major (Al, Fe, Ca, Mg, Na, K, P, Si, Ti), trace elements (As, Ba, Be, Co, Cr, Cu, Mo, Mn, Ni, Pb, Sc, V, Y, Zn, Zr, Ga) and compared with Upper continental crust (UCC), source area composition and local background values. The elemental concentrations were comparable with the average andesite and dacitic composition of the source area and the local background values except for enrichment of Cu (56.27. ppm), Pb (34. ppm) and Zn (235.64. ppm) in the downstream sediments suggesting a significant external influence (anthropogenic). The fluvial sediments of Atoyac River basin display low CIA and PIA values implying predominantly weak to moderate weathering conditions in the source region. Based on the provenance discrimination diagrams and elemental ratios, it is understood that the collected sediments are derived from intermediate to felsic volcanic rocks dominated in the study region. Metal contamination indices highlight the enrichment of Cu, Pb, Zn, Mo, Cr and S clearly indicating the influences from natural (weathering and volcanic activity) and external (anthropogenic) sources. Ecological risk assessment results indicate that Cr, Ni and Zn will cause adverse biological effects to the riverine environment.